2010
DOI: 10.1016/j.juro.2010.03.040
|View full text |Cite
|
Sign up to set email alerts
|

Scribes in an Ambulatory Urology Practice: Patient and Physician Satisfaction

Abstract: Electronic medical record scribes in a urology practice may be a practical solution to provide documentation while maintaining or improving the doctor-patient relationship because they increase physician satisfaction and do not detract from patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
89
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(94 citation statements)
references
References 6 publications
4
89
0
1
Order By: Relevance
“…As shown in Figure 1, application of exclusion criteria resulted in 5 studies for this review. Four studies were identified using the database search [25][26][27][28] and 1 through Google Scholar. 29 No additional studies were identified by searching the included studies' reference lists or the forward publication search.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Figure 1, application of exclusion criteria resulted in 5 studies for this review. Four studies were identified using the database search [25][26][27][28] and 1 through Google Scholar. 29 No additional studies were identified by searching the included studies' reference lists or the forward publication search.…”
Section: Resultsmentioning
confidence: 99%
“…27 and 1 in a urology clinic. 26 Each study setting was affiliated with a larger academic health center, 25,26,29 health care organization, 27 or community hospital.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3] Recent research, however, describes workflow inefficiencies, reduced satisfaction, 4,5 and clinician concerns 6 in relation to using electronic communication systems. 7 Mayo Clinic believes in providing quality, patient-centered care and creating a health care workforce of the future to align with its core values.…”
Section: Introductionmentioning
confidence: 99%